Pengaruh Motivasi dan Lingkungan Kerja terhadap Kinerja Karyawan pada PT. Price Trandos Engineering - Susanto, Noto; Pratama, Guruh Dwi; Anggraini, Ninik; Nuraldy, Hafis Laksmana; Rachmawan, Ade (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
The aim of this study is to determine the effect of motivation and work environment on employee performance at PT. Price Trandos Engineering, both partially and simultaneously. The research employs a quantitative method, with saturated sampling technique involving 58 respondents. The data analysis techniques used in this study include validity testing, reliability testing, classical assumption testing, simple linear regression testing, multiple linear regression testing, coefficient of determination, t-test hypothesis testing, and f-test hypothesis testing. The results show that motivation has a significant effect on employee performance. A strong correlation was found between the two variables, indicating that motivation plays a substantial role in influencing employee performance. The hypothesis testing confirmed that the effect of motivation on performance was significant, as the t-test result supported the rejection of the null hypothesis. Similarly, the work environment also has a significant effect on employee performance. A moderate correlation was observed between the work environment and performance, suggesting that improvements in the work environment can enhance employee performance. The hypothesis testing for the work environment variable also showed significant results, leading to the rejection of the null hypothesis. Furthermore, both motivation and work environment have a significant simultaneous effect on employee performance. The results indicated a strong relationship between the independent variables (motivation and work environment) and the dependent variable (employee performance). The hypothesis testing confirmed the simultaneous impact of these two factors on performance, leading to the rejection of the null hypothesis.